Torbangun Leaves (Coleus amboinicus Lour) Powder Capsules Supplementation Improve Lipid Profile and Blood Pressure in Men with Hypercholesterol - Amalia, Niken Rizki; Damanik, Muhammad Rizal Martua; Ekayanti, Ikeu (Jurnal Gizi dan Pangan, 2018)
The aim of this study was to analyze the effect of torbangun leaves powder capsules supplementation on lipid profile and blood pressure in men with hypercholesterol. This study was a single blind randomized control trial design with 26 male subjects. The inclusion criterias for subject were adults (age 25-55 years), blood total cholesterol levels ≥200 mg/dl, and signed the informed consent. Subjects were divided into two groups of one intervention (torbangun capsules) and one control (amylum) group. The intervention of 750 mg/day torbangun powder for the intervention group and 300 mg/day amylum for control group were administered for 28 days. The analysis of lipid profile results showed that the trygliseride, LDL, and HDL were not significantly affected by the torbangun intervention but it significantly decreased the total cholesterol level. The supplementation of torbangun capsules also decreased the sistolic blood pressure significantly. but not in diastolic pressure.